2018
DOI: 10.7717/peerj.4606
|View full text |Cite
|
Sign up to set email alerts
|

Can phosphorus application and cover cropping alter arbuscular mycorrhizal fungal communities and soybean performance after a five-year phosphorus-unfertilized crop rotational system?

Abstract: BackgroundUnderstanding diversity of arbuscular mycorrhizal fungi (AMF) is important for optimizing their role for phosphorus (P) nutrition of soybeans (Glycine max (L.) Merr.) in P-limited soils. However, it is not clear how soybean growth and P nutrition is related to AMF colonization and diversity of AMF communities in a continuous P-unfertilized cover cropping system. Thus, we investigated the impact of P-application and cover cropping on the interaction among AMF colonization, AMF diversity in soybean roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 75 publications
(93 reference statements)
5
19
0
1
Order By: Relevance
“…Overall, our study showed a stimulation of AMF in the subsequent crop when fallow was replaced by barley CC but not when fallow was replaced by vetch. Our results agreed with other field experiments in which the use of grass CCs, such as winter wheat ( Kabir and Koide , ; Higo et al, ), oat and rye ( Kabir and Koide , ; White and Weil , ), and ryegrass ( Higo et al, ), increased mycorrhizal colonization from 26% to two times in the subsequent maize crop. The lack of positive effect of vetch CC on the AMF parameters is contrary to our first hypothesis and disagrees with some studies.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our study showed a stimulation of AMF in the subsequent crop when fallow was replaced by barley CC but not when fallow was replaced by vetch. Our results agreed with other field experiments in which the use of grass CCs, such as winter wheat ( Kabir and Koide , ; Higo et al, ), oat and rye ( Kabir and Koide , ; White and Weil , ), and ryegrass ( Higo et al, ), increased mycorrhizal colonization from 26% to two times in the subsequent maize crop. The lack of positive effect of vetch CC on the AMF parameters is contrary to our first hypothesis and disagrees with some studies.…”
Section: Discussionsupporting
confidence: 92%
“…To characterize the AMF community in the tomato roots, we performed high-throughput sequencing of amplicons as described in Higo et al [15,43,48]. Briefly, three PCR products per plot were combined together (from 27 samples to 9 samples) to prepare 9 libraries.…”
Section: Amplicon Sequencing For Amf Communities In Rootsmentioning
confidence: 99%
“…The taste and flavor of tomatoes and their antioxidant content differ according to growing conditions, cultivation techniques, cultivars, and cultivation time [10][11][12][13]. Soil P is a well-known key nutrient for tomato production and other crops, such as maize [14] and soybean [15], and maintaining adequate levels of P in the soil is important for maximizing tomato growth and development [16][17][18]. However, the effect of different P fertilizer amounts on the growth performance of tomato plants remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations